Spatio‐temporal dynamics of nutrients at the water‐sediment interface: case of the Nokoue lagoon in Southern Ben - Socohou, Akilou; Djihouessi, Metogbe Belfrid; Tigo, Béatrix Amen; Viainon, Vignon; ADANDEDJI, Firmin M.; ADOUNKPE, Julien G.; Aina, Martin Pepin (My University, 2023)
Lake Nokoué, a major component of the hydrographic system of the Ouémé delta, is the larg- est lagoon-estuarine ecosystem in Benin. Recent stud- ies have shown that benthic processes would actively participate in the maintenance of the eutrophication and biogeochemical cycle of this ecosystem. In order to understand the implication of the bottom on the quality of the waters of the lake, a monthly follow-up of ten (10) parameters of quality of the waters of the bottom was undertaken from July 2020 to December 2021 on a network of nineteen (19) stations distrib- uted on the whole lake. Univariate and multivariate analysis techniques were used to assess the spatial and temporal dynamics of these waters. The Kruskal– Wallis test, PCA, correlation analysis and discri- minant analysis all showed a very marked influence of the hydrological regime on the concentration of nutrients compared to the influence of anthropo- genic activities around the lake and an influence of climatic conditions on internal processes. Indeed, water inflows from the Ouémé watershed are the main contributors of phosphorus in the lake while ben- thic processes are the most important contributors of nitrogen. Cluster analysis defined three significantly different areas in Lake Nokoué: the channel, the cen- tre of the lake and the river mouth. A single station in each cluster could be used for a spatial assessment of water quality over the entire lake.
Keywords: Lake Nokoué · Eutrophication · Benthic processes · Multivariate analysis · Nitrogen · Phosphorus